Utilização de filme de baixa permeabilidade ao oxigênio no revestimento das paredes de silos trincheira - Santos, Josiane Pereira dos (2015)
This work was conducted with the objective of evaluating the effect of trench silo wall covering with low permeability to oxygen (LPF) over the loss of dry matter, chemical composition and the populations of yeast and filamentous fungi in maize silage. Four masonry trench type silos were longitudinally divided. One of the walls was coated with the LPF while the other remained with no covering. Each silo was divided into three sections, allocating seven nylon bags in each section. One bag in the central zone and six bags in the peripheral zone of the silo, with three in each longitudinal part. The distances of the bags in relation to the silo was of between 0 and 0.50 m; between 0.51 and 1.0 m; and between 41.01 and 1.50 m, characterized with as positions 1, 2 and 3, respectively. The experimental design was in randomized blocks, with four blocks, seven treatments and three replicates. The PROC MIXED resource of the SAS program was used and the data submitted to an orthogonal contrast with the T test at a 5% level of significance. The wall covering with LPF obtained a silage with higher lactic acid content, lower pH and higher TDN and dairy production estimates. The population of yeast and filamentous fungi were smaller in the silages maintained under the new sealing strategy, and the losses of DM were also lower. Of the three studied positions, position 1 presented higher concentration of lactic acid, lower pH, higher starch concentration, better NDFD and higher estimates for the values of TDN and dairy production. The lower penetration of oxygen provided silages with low yeast counts in all three positions and of filamentous fungi in position 1 and 2 in the silages under sealing. The new sealing strategy decreased the entrance of oxygen and reduced the development of yeast and filamentous fungi, attenuating the negative effects these cause over microbiological and nutritional quality of maize silage during the use of the silo.